Bridging the Gap: Making Sense of the Disaccord between Migrants’ Education and Occupation - Waldendorf, Anica (Social Inclusion, 2021)
Social mobility is a central topic of interest within sociology and whilst it has been theoretically linked to spatial mobility, there is still little empirical research on the interplay between the two. Using a subsample of highly educated family migrants from a German mixed-methods project, this study qualitatively analyses the impact of geographical mobility on objective social position and on its subjective perception. Six qualitative interviews are analysed and supplemented with descriptive quantitative data from the German Socio-Economic Panel to firstly, reconstruct the spatial mobility trajectories of the individuals and secondly, determine their social position in Germany and ascertain whether they experienced occupational downgrading. These two analyses are integrated to explore how respondents experienced their change in social position. Across the board, respondents migrated as young adults, before or shortly after labour market entry. Five of the participants experienced occupational downgrading. Strikingly, this objective downgrading, whilst acknowledged, was not perceived negatively. The participants constructed a narrative that employed three legitimation strategies to cast their current social position in a positive light: (1) emphasising the rights, stability and security that they experience in Germany, (2) drawing attention to the economic improvement that they experienced and (3) displaying an inner attitude that is marked by modest life aspirations and a high regard for leisure time. By drawing on multinational frames of reference and thus drawing comparisons between their home country and Germany, participants highlighted the experienced benefits.